2022
DOI: 10.3390/jcm11154418
|View full text |Cite
|
Sign up to set email alerts
|

IOL Power Calculations and Cataract Surgery in Eyes with Previous Small Incision Lenticule Extraction

Abstract: Small incision lenticule extraction (SMILE), with over 5 million procedures globally performed, will challenge ophthalmologists in the foreseeable future with accurate intraocular lens power calculations in an ageing population. After more than one decade since the introduction of SMILE, only one case report of cataract surgery with IOL implantation after SMILE is present in the peer-reviewed literature. Hence, the scope of the present multicenter study was to compare the IOL power calculation accuracy in post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
5
17
0
Order By: Relevance
“…Regarding the variance of the mean PE by ray tracing, the results of Lischke et al yielded a very small variance of 0.23 D 2 . 10 These results were in accordance with our study, yielding a mean PE variance by Okulix of 0.205 D 2 . These results indicate high precision and reliability of ray tracing with Okulix in IOL power calculation after SMILE.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding the variance of the mean PE by ray tracing, the results of Lischke et al yielded a very small variance of 0.23 D 2 . 10 These results were in accordance with our study, yielding a mean PE variance by Okulix of 0.205 D 2 . These results indicate high precision and reliability of ray tracing with Okulix in IOL power calculation after SMILE.…”
Section: Discussionsupporting
confidence: 92%
“…The high variance of 1.63 D 2 obtained with Haigis-L reported by Lischke et al can be attributed to the small amount of eyes, which is strongly influenced by outliers (range of mean PE ranges from À3.76 to 1.17 D). 10 Lischke et al reported, to the authors' knowledge, for the first time, the results of IOL calculations in pseudophakic eyes after SMILE. 10 Although the number of eyes examined in the study conducted by Lischke et al is very small, these results most likely indicate that Haigis-L is not among the most accurate formulas for IOL calculation after SMILE.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Minor incision cataract surgery can effectively reduce the risk of postoperative intraocular inflammation and is an essential type of cataract surgery [ 39 ]. To meet the demands of minor incision surgery, the materials used to prepare IOLs must have excellent bending, folding, and shape recovery properties.…”
Section: Resultsmentioning
confidence: 99%